Ecological control of atmospheric air contamination on the objects of aviation fuel supply - Матвеева, Е. Л. (Proceedings of National Aviation University (archive), 1999)
Considered are the problems of necessity of organization of ecological policy at a level of an airenterprise, with the purpose of reduction of harmful effect of an antropogeneous load on an environment, diminution of harmful effect of aviation fuel and lubricating materials on safety of work, reduction of losses of oil products